FAKTOR PENYEBAB KURANG LANCARNYA REMAJA AWAL DALAM MELAKSANAKAN TUGAS-TUGAS PERKEMBANGAN DI SMP NEGERI 25 PADANG - Maiyuniati, Maiyuniati; Helma, Helma; Alfaiz, Alfaiz (Bimbingan dan Konseling, 2014)
Many learners who do not understand the developmental tasks, learners are less able to control themselves and learners lack of freedom. The purpose of this study is to describe the physical growth factors, and psychological factors that lead to the development of early adolescents are less smooth in carrying out development tasks. This study is a quantitative descriptive approach. The study population includes all students at Junior High School 25 Padang 750 learners with 88 samples of learners. The results of this study revealed that the factors causing the lack of smoothness in performing early adolescent developmental tasks is adolescent physical development 42.25%, factor of adolescent psychological development 34.09%, position in the family adolescents 47.73%, teenagers the opportunity to study the developmental tasks of 38.54%, motivation self 31.82%, the smooth implementation of developmental tasks during the previous 52.27%.